Metacognitive and Conceptual Understanding of Pteridophytes: Development and Validity Testing of an integrated Assessment Tool - Puji Lestari; Rizhal Hendi Ristanto; Mieke Miarsyah (Indonesian Journal of Biology Education, 2019)
The use of question instrument in determining achievement of students’ study goal can be referred from the score achieved by the students in solving contextual questions with solution or solving strategy in high level of thinking. The research aims to get integrated assessment toolsof conceptual understanding of Pteridophyta and metacognitive skill that is validated and can be used in learning activity. The research is conducted in July 2018 – November 2019 at Universitas Negeri Jakarta, course of Botany Cryptogamae, sub-course Pteridophytes. This is a Research and Development study using 4D method (Define, Design, Develop, and Disseminate). However, the research will be conducted up to the develop phase only. The result shows that integrated assessment toolon conceptualunderstanding of Pteridophytesand students’ metacognitive skill is proper to be used, with expert validation result shows 78.13 on criteria for concept understanding, and 79.17 for students’ metacognitive skill. Result of instrument validation shows more than 0.396, means it is valid, and reliability more than 0.6.